Socio-Cultural Factors of the Effective use of Critical Thinking in the Development of Modern Legal Knowledge - Nuritdinov, Navruz (Pubmedia Social Sciences and Humanities, 2024)
In the effective use of critical thinking in the development of modern legal knowledge, socio-cultural factors are of great importance. These factors shape the ways in which lawyers and scientists approach problems, interpret laws, and implement solutions. Educational systems that prioritize critical thinking skills in curricula, especially in law schools, produce skilled graduates in analytical thinking and problem solving.